Internacionalização de empresa: aceleração das born globals sob a perspectiva das capacidades dinâmicas - Oliveira, Izadora Ribeiro e Garcia de (2021)
The aim of this dissertation is to carry out an in-depth analysis of the born globals phenomenon, and to identify strategies that contribute to the acceleration of the internationalization of young companies from emerging countries. To this end, the following question arises: How did Dynamic Capacities contribute to the configuration of strategies of born globals in Brazil, in an accelerated way? From this problem, it was defined as a general objective of the work to study the influence of Dynamic Capabilities as a contribution to the configuration of strategies that enable the acceleration of born globals in Brazil. For this, a qualitative approach was used, with a single case study method. The empirical field of work is a digital company, from an emerging country, Brazil. The data were primary and secondary and the form of data analysis used was content analysis. The main notes brought are that the main strategies practiced by the born globals, from the perspective of Dynamic Capabilities, are the following: create, innovate, reconfigure and modify. However, the work makes a contribution by adding the cultural perspective, considered of utmost importance in the internationalization process of born globals.